Migration, Refugees and Human Security in the Mediterranean and MENA (Springer International Publishing, 2018)
This book focuses on the Mediterranean/MENA migration crisis and explores the human security implications for migrants and refugees in this troubled region. Since the Arab uprisings of 2010/2011, the Middle East and North Africa region has experienced major political transformations and called into question the legitimacy of states in the region. Displaced populations continue to suffer due to the major conflicts in Syria, Iraq and elsewhere, causing fragmentation and dis-integration of communities. Contributors to this volume analyze how and why this crisis differs significantly from previous migration/refugee flows in the region, explain the historical and political antecedents of this crisis which have played a part in its shaping, and explore the relationship between human security and the protection of vulnerable individuals and groups. Marion Boulby is Associate Professor of History at Trent University, Canada. Kenneth Christie is Professor and Program Head of the Masters in Arts in Human Security and Peacebuilding at Royal Roads University, Canada.